Integrated Technical, Thermal, and Techno-Economic Assessment of Hot-Oil and Electric Heating Systems for 15–22 MT Asphalt Storage Tanks - Arifuddin Arifuddin; Elbi Wiseno (International Journal Science and Technology, 2026)
The selection of an appropriate heating system for asphalt storage tanks plays a critical role in determining operational efficiency, maintenance requirements, energy consumption, and long-term investment performance in asphalt production facilities. Conventional hot-oil heating systems have been widely implemented because of their ability to provide uniform heat distribution; however, they require complex auxiliary equipment, continuous fuel consumption, and intensive maintenance. Consequently, evaluating alternative heating technologies has become increasingly important for improving industrial efficiency and reducing operating costs. Objective: This study aims to compare the technical design, thermal performance, and economic performance of hot-oil and electric heating systems for asphalt storage tanks with capacities ranging from 15 to 22 MT in order to identify the most suitable engineering solution for medium-capacity applications. Methodology: This research employed a quantitative comparative engineering approach using validated secondary engineering data, industrial equipment specifications, and operating-cost assumptions. The analysis included comparisons of technical design characteristics, initial investment, annual operating costs, payback period, ten-year life-cycle cost, and thermal-performance indicators under identical operating conditions. Findings: The results indicate that the electric-heating system provides a simpler engineering configuration, shorter installation time, lower maintenance requirements, and higher temperature-control accuracy than the hot-oil system. Economically, the electric-heating system reduces annual operating costs by approximately IDR 661.34 million, achieves a simple payback period of approximately 0.38 years (4.5 months), and lowers the ten-year life-cycle cost by approximately IDR 6.86 billion. Furthermore, the electric-heating system maintains nearly 100% point-of-use thermal efficiency, whereas the efficiency of the hot-oil system decreases over time because of combustion losses and equipment ageing. Implications: The findings provide practical engineering guidance for selecting heating systems in asphalt storage facilities by demonstrating that electric heating can improve operational efficiency while reducing long-term investment and maintenance costs. The results may also support engineering decision-making related to industrial process electrification. Originality: The originality of this study lies in the integration of technical design comparison, thermal-performance evaluation, and comprehensive techno-economic analysis into a unified engineering assessment framework for medium-capacity asphalt storage tanks. This integrated approach provides a practical reference for engineers and decision-makers considering the modernization of industrial asphalt-heating systems.